2021
DOI: 10.1088/1742-6596/1871/1/012075
|View full text |Cite
|
Sign up to set email alerts
|

An Automatic Recognition Method of Fruits and Vegetables Based on Depthwise Separable Convolution Neural Network

Abstract: Traditional fruit and vegetable classification is mostly based on manual operation, which is inefficient. Deep convolution neural network shows excellent performance in feature learning and expression. In this paper, an automatic recognition system of fruits and vegetables based on deep convolution neural network is designed. By using depthwise separable convolution instead of the traditional standard convolution, a neural network is constructed with less parameters, which is suitable for equipment with limite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Each attribute needs to be coded as a feature. The likelihood probability of the existence of scenario attributes is used to evaluate the coding, as shown in Equation (5).…”
Section: Tourism Scenario Attribute-oriented Semantic Feature Relatio...mentioning
confidence: 99%
See 1 more Smart Citation
“…Each attribute needs to be coded as a feature. The likelihood probability of the existence of scenario attributes is used to evaluate the coding, as shown in Equation (5).…”
Section: Tourism Scenario Attribute-oriented Semantic Feature Relatio...mentioning
confidence: 99%
“…They achieved the goal of cross-media semantic space sharing. Meanwhile, the crossmedia scenes were uniformly represented to construct the cross-media scenario recognition dataset [5]. Zhang et al (2022) proposed a CMR knowledge transfer method based on Deep Learning (DL) [6].…”
Section: Introductionmentioning
confidence: 99%
“…The standard convolution is decomposed into deep convolution and point-wise convolution by depth-separable convolution [23][24][25]. First, each channel of the input…”
Section: Depth-separable Convolutionmentioning
confidence: 99%
“…One is to make the network efficient without deepening the number of network layers, the other is to improve the phase unwrapping performance of the network and retain more image details. In terms of optimize networks, existing research has demonstrated that depthwise separable convolution (DSC) module [32] is effective in significantly reducing the number of parameters. On the second aspect, it is shown that adding atrous spatial pyramid pooling (ASPP) [33] module to the network is beneficial for expanding the feature receptive field.…”
Section: Introductionmentioning
confidence: 99%